Correlations between body composition, aerobic capacity, speed and distance covered among professional soccer players during official matches - Radziminski, L.; Szwarc, A.; Padrón-Cabo, A.; Jastrzebski, Z. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: The importance of sprinting and high-speed running activities during a soccer match is indisputable. The main purpose of this study was to investigate the relations between the players` speed, aerobic capacity, body composition and distance covered in different speed zones during official soccer matches and to compare the match performance variables according to playing position. METHODS: Twenty-three professional soccer players (age: 27.9±4.58 y, body mass: 78.8±7.35 kg, height: 181.7±6.53 cm) participated in this study. During 13 weeks of the competitive season, players participated in 16 official matches and completed body composition analyses, sprint tests, multistage shuttle run tests (MST), and incremental running tests (IRTs). RESULTS: Significant negative correlations were found between sprint distance and percent of fat mass (FM; r=-0.57, P<0.0001), MST (r=0.45, P<0.001), maximal speed (r=0.44, P<0.001). High-speed running (HSR) distance covered by the players during the matches was significantly correlated with FM (r=-0.38, P<0.001) and MST distance (r=0.30, P<0.01). CONCLUSIONS: These data indicate that professional soccer players with lower fat content and higher levels of aerobic capacity are able to cover longer distances in sprinting and HSR during official matches.